2016
DOI: 10.1103/physrevapplied.6.054008
|View full text |Cite
|
Sign up to set email alerts
|

Drift-Diffusion Studies of Compositional Morphology in Bulk Heterojunctions: The Role of the Mixed Phase in Photovoltaic Performance

Abstract: The active layers of most OPV devices are constructed from a blend of two organic compounds. The two materials spontaneously segregate into pure component phases during device fabrication, creating a bicontinuous network of conduction pathways that are selective for electron or hole charge carriers. The morphological distribution of these materials within the active layer has long been known to influence charge transport and resulting device performance. In addition to the two purecomponent phases present in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 59 publications
(88 reference statements)
2
13
0
Order By: Relevance
“…13,[21][22][23][24][25] In addition, the nature of the morphological distribution in the donor-acceptor interface, whether blurred with a continuous composition gradient or presenting an abrupt transition between the donor and acceptor phase, was predicted to affect the efficiency of exciton harvesting and charge extraction, thus impacting upon the overall device performance. 23,26,27 A key uncertainty in such analyses is the nature of the interfacial bound charges in such bulk heterojunction (BHJ) devices and their impact upon charge generation and recombination.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13,[21][22][23][24][25] In addition, the nature of the morphological distribution in the donor-acceptor interface, whether blurred with a continuous composition gradient or presenting an abrupt transition between the donor and acceptor phase, was predicted to affect the efficiency of exciton harvesting and charge extraction, thus impacting upon the overall device performance. 23,26,27 A key uncertainty in such analyses is the nature of the interfacial bound charges in such bulk heterojunction (BHJ) devices and their impact upon charge generation and recombination.…”
mentioning
confidence: 99%
“…These observations are consistent with a recent semi-empirical theoretical study of the effect of intermixed regions upon charge recombination. 27 In contrast, in the non-intercalated 1:1 PBTTT:ICTA system, there is a shallow energetic barrier to separate the interfacial CT state, and yet most of the photogenerated charge carriers are either morphologically bound or energetically trapped charges in a more disordered blend. 37 As a consequence, polaron recombination as obtained by TAS is first order, and the EGE remains at a low level independently of the applied voltage.…”
mentioning
confidence: 99%
“…In general, the changes observed in surface roughness may be a consequence of bulk morphology changes induced by the coating-temperature variations that influence the drying kinetics [41]. The hot drum and hot slot-die head induce highly ordered molecular packing [24], which improves carrier transport inside the bulk heterojunction [24,25,42], improving J SC and FF (Table I).…”
Section: -5mentioning
confidence: 99%
“…[80,[120][121][122][123][124] There are two types of disorder, which can affect OSC device performance in different ways: energetic disorder, which is usually a consequence of the conformational freedom of the molecules or polymer chains, and structural disorder, results from the BHJ phase separation that can lead to "dead-ends" and other morphological conditions that are not optimal for carrier transport. [125] Several studies have examined the effects of energetic disorder on OSC performance, usually assuming a Gaussian distribution of energetic states or an exponential tail of trap states in 1D drift-diffusion simulations. [123,124] Martin et al [130] suggested an ideal ordered BHJ for the 2D drift-diffusion simulation.…”
Section: Compositional Morphology In Bulk Heterojunctionsmentioning
confidence: 99%
“…Finck and Schwartz also simulated the effects of DA mixed-composition by utilizing morphologies generated by Cahn-Hilliard (CH) modeling [131] of binary fluid phase separation. [125] With the CH model, the component domain sizes can be tuned with a single parameter. Then, a mixed interfacial region by smoothing the binary morphology in a continuously controllable fashion can be introduced.…”
Section: )mentioning
confidence: 99%